The Aesthetic Experience : an Anthropologist Looks at the Visual Arts. - Maquet, Jacques (New Haven and London : Yale University Press London Yale University Press New Haven, 1986)
Albright, Ivan Le Lorraine ; Alfaro Siqueiros, David ; Arp, Hans (Jean) ; Bacon, Francis ; Beasley, Bruce ; Botticelli, Sandro ; Brancusi, Constantin ; Braque, Georges ; Breuer, Marcel ; Calder, Alexander ; Courbet, Gustave ; Delvaux, Paul ; Derain, André ; Diebenkorn, Richard ; El Greco ; Etrog, Sorel ; Goncharova, Natalia ; Gottlieb, Adolph ; Graham, Robert ; Hepworth, Barbara ; Hopper, Edward ; Hunt, Richard ; Kandinsky, Wassily ; Kirchner, Ernst Ludwig ; Klimt, Gustav ; de Kooning, Willem ; Larionov, Michail ; Lichtenstein, Roy ; Louis, Morris ; Malevich, Kasimir ; Mies van der Rohe, Ludwig ; Modigliani, Amedeo ; Mondriaan, Piet ; Moore, Henri ; Munch, Edvard ; Noland, Kenneth ; Pevsner, Antoine ; Picasso, Pablo ; Pollock, Jackson ; Ramos, Mel ; Rauschenberg, Robert ; Rodchenko, Alexander ; Rothko, Mark ; Tatlin, Vladimir ; Thonet (factory design) ; Titiaan ; Tobey, Mark ; Vasarely, Victor ; Warhol, Andy ; Wesselmann, Tom
Engels
boek